Numerical investigation of cavitation performance on bulb tubular turbine. Issue 1 (May 2016) - Sun, L G; Guo, P C; Zheng, X B; Luo, X Q
Abstract: The cavitation flow phenomena may occur in the bulb tubular turbine at some certain operation conditions, which even decrease the performance of units and causes insatiably noise and vibration when it goes worse. A steady cavitating flow numerical simulations study is carried out on the bulb tubular unit with the same blade pitch angle and different guide vane openings by using the commercial code ANSYS CFX in this paper. The phenomena of cavitation induction areas and development process are obtained and draws cavitation performance curves. The numerical results show that the travelling bubble cavity is the main types of cavitation development over a wide operating range of discharge and this type of cavitation begins to sensitive to the value of cavitation number when the discharge exceeding a certain valve, in this condition, it can lead to a severe free bubble formation with the gradually decrement of cavitation number. The reported cavitation performance curves results indicate that the flow blockage incident would happen because of a mount of free bubble formation in the flow passage when the cavity developed to certain extend, which caused head drop behavior and power broken dramatically and influenced the output power.